2019
DOI: 10.1158/1078-0432.ccr-18-4140
|View full text |Cite
|
Sign up to set email alerts
|

MYC-Driven Small-Cell Lung Cancer is Metabolically Distinct and Vulnerable to Arginine Depletion

Abstract: Purpose: Small-cell lung cancer (SCLC) has been treated clinically as a homogeneous disease, but recent discoveries suggest that SCLC is heterogeneous. Whether metabolic differences exist among SCLC subtypes is largely unexplored. In this study, we aimed to determine whether metabolic vulnerabilities exist between SCLC subtypes that can be therapeutically exploited.Experimental Design: We performed steady state metabolomics on tumors isolated from distinct genetically engineered mouse models (GEMM) representin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
124
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 55 publications
9
124
0
Order By: Relevance
“…Increased glycolytic activity is thought to help satisfy the rapacious demands of highly proliferative cancer cells for biosynthetic precursors including lipids, proteins and nucleic acids. However, this altered metabolism can leave tumors vulnerable to metabolic disruptions such as starvation of substrates including glucose, asparagine, glutamine, methionine, serine and others (Chalishazar et al, 2019;Gao et al, 2019;Graham et al, 2012;Joly et al, 2020;Maddocks et al, 2013;Wise et al, 2008;Yuneva et al, 2007). Therefore, understanding the interplay between oncogenes and metabolism is essential to understand how to design therapeutic strategies targeting tumor metabolism (Galluzzi et al, 2013;Martinez-Outschoorn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increased glycolytic activity is thought to help satisfy the rapacious demands of highly proliferative cancer cells for biosynthetic precursors including lipids, proteins and nucleic acids. However, this altered metabolism can leave tumors vulnerable to metabolic disruptions such as starvation of substrates including glucose, asparagine, glutamine, methionine, serine and others (Chalishazar et al, 2019;Gao et al, 2019;Graham et al, 2012;Joly et al, 2020;Maddocks et al, 2013;Wise et al, 2008;Yuneva et al, 2007). Therefore, understanding the interplay between oncogenes and metabolism is essential to understand how to design therapeutic strategies targeting tumor metabolism (Galluzzi et al, 2013;Martinez-Outschoorn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chemotherapy‐resistant cells are more likely to have high levels of C‐MYC and are more sensitive to arginine depletion. In mouse models of SCLC, depleting arginine had no effect on survival in mice with L‐MYC–driven tumors, but was significantly better than chemotherapy in improving the survival in mice with C‐MYC–driven tumors …”
Section: Arginine Dependence Of Myc‐driven Lung Cancermentioning
confidence: 97%
“…Steady‐state metabolomic profiling in collaboration with Ralph DeBerardinis's laboratory has shown that C‐MYC–driven tumors are metabolically distinct from L‐MYC–driven tumors . C‐MYC–driven tumors show an enrichment in nucleotide biosynthesis and arginine metabolism .…”
Section: Arginine Dependence Of Myc‐driven Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations